KEEFEKTIFAN TEKNIK DISKUSI UNTUK MENINGKATKAN KECERDASAN INTERPERSONAL - Hermawan, Rian; Fadhilah, Siti Sutarmi; Muslim, Mudaris (Consilium: Jurnal Program Studi Bimbingan dan Konseling, 2014)
This research aims to know the effectiveness of group guidance service by using discussion technique to improve interpersonal intelligence of the eighth grade learners of Junior High School in Sragen. Based on the hypothesis test with the score of tcount=2,703>ttable=1.67 which means Ho was rejected and Ha is accepted, thus the group guidance service by using discussion technique is effective to improve interpersonal intelligence of the eighth grade learners of Junior High School in Sragen. In conclusion, the group guidance service by using discussion technique is effective to improve interpersonal intelligence of students.